KINERJA LEMBAGA PEMBERDAYAAN MASYARAKAT DESA (LPMD) DALAM MENINGKATKAN POTENSI DESA (Studi Di Desa Matawine Kecamatan Lakudo Kabupaten Buton Tengah) - Muliati, Muliati; Darpin, Darpin; Muhammad Elwan, La Ode (Universitas Halu Oleo, 2020)
This research is a descriptive qualitative research method and is supported by primary data sources and secondary data. In determining the informants of this study using purposive sampling, amounting to 9 people consisting of village head, village secretary, LPMD chairman, 3 LPMD members, and 3 communities. The results showed that the Performance of the Village Community Empowerment Institution (LPMD) in Increasing Village Potential can be seen from the performance measurement indicators according to Moeheriono as follows: (1) Responsibility of the Desa LPMD Matawine lack of socialization conducted by LPMD to the community and the slow response to the community's needs; (2) Responsibility of LPMD Desa Matawine, not all LPMD management occupy their positions in accordance with their fields and there is no guidance from the village government for LPMD; (3) Accountability of Desa Matawine LPMD lack of documents such as the absence of LPMD management from each meeting or meeting and in terms of accountability for the implementation of development such as the construction of tourist roads and mangrove tourism development.